Proposal of an international harmonized analytical technique for quantifying of residual acetamiprid and imidacloprid in wheat - Furusawa, Naoto (International Journal of Advanced Chemistry, 2015)
This paper proposes an international harmonized analytical method for residual monitoring of selected neonicotinoids in crops and presents a fast, easy, and space-saving technique of sample preparation followed by a 100% water mobile phase high-performance liquid chromatography (HPLC) coupled photo-diode array detector (PDA) for quantifying acetamiprid (ATP) and imidacloprid (ICP) in wheat. The analytes were extracted from the sample using a handheld ultrasonic homogenizer with water, and purified by MonoSpinÂ® C18-CX, a centrifugal monolithic silica spin mini-column, and quantified within 20 min/sample. The accuracy, precision, and system suitability are well within the international method acceptance criteria.